Волинезнавча тематика у видавничих програмах періодики громадських товариств Правобережної України (остання третина ХІХ - початок ХХ ст.) - Заєць, Любов; Zaiets, Liubov (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті йдеться про мету заснування періодичних видань громадських товариств Правобережної України останньої третини ХІХ – початку ХХ ст., їх установчі документи, втілення в життя задумів щодо функціонування того чи іншого друкованого органу. Звернено увагу на тематичну спрямованість видань та частку публікацій у часописах з історії та культурної спадщини Волині.

The article deals with the purpose of the periodicals’ foundation of the public societies in Right-bank Ukraine (the last third of the 19th century – the beginning of the 20th century). The editorial programmes are outlined here. The article mentions the Ukrainian direction of the following published works ‘The Proceedings of the South-Western Department of the Russian Imperial Geographic Society’, ‘Nestor the Chronicler Historical Society Readings’, ‘Kyiv Antiques’, ‘Archaeological Chronicles of South Russia’, ‘Transactions of the Volyn Researchers Society’, and ‘The Proceedings of the Ukrainian Science Society in Kyiv’. Pro-Russian and pro-governmental direction is inherent to such editorial programmes as ‘Volyn History and Archeology Collection’, ‘The Proceedings of the Podol Ecclesiastical History and Archeology Society’, and ‘Military History Bulletin’. The article draws attention to the subject-matter of the periodicals and the published works devoted to the history and the cultural heritage of the Volyn region.
Volyn Region Research Subject-matter in Editorial Periodical Programmes of the Public Societies in Right-bank Ukraine (the Last Third of the 19th Century – the Beginning of the 20th Century)
Keywords: Волинь; товариство; періодика; видавнича програма; культурна спадщина; Volyn region; a society; periodicals; an editorial programme; a cultural heritage